Computational Characteristics of Production Seismic Migration and its Performance on Novel Processor Architectures - Panetta, Jairo; Souza Filho, Paulo R. P. de; Cunha Filho, Carlos A. da; Motta, Fernando M. Roxo da; Pinheiro, Silvio Sinedino; Pedrosa Junior, Ivan; Rosa, Andre L. Romanelli; Monnerat, Luiz R.; Carneiro, Leandro T.; Albrecht, Carlos H. B. de (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2007: Anais do XIX International Symposium on Computer Architecture and High Performance Computing, 2007)
We describe the computational characteristics of the Kirchhoff prestack seismic migration currently used in daily production runs at Petrobras and its port to novel architectures. Fully developed in house, this portable and fault tolerant application has high sequential and parallel efficiency, with parallel scalability tested up to 8192 processors on the IBM Blue Gene without exhausting parallelism. Production load comprises thousands of jobs per year, consuming the installed park of a few thousand x86 CPU cores, with top production runs continuously using up to 1000 dedicated processors during 20 days. A built in mechanism automatically produces, collects and stores job performance data, allowing single job performance analysis and multi job performance statistics. Its port to quad-core x86 and Sony PlayStation 3 achieved very high price/performance and performance/watt gains over single core x86 machines. Port to the PS3 is described in detail. Experimental performance data on a modest PS3 cluster is also presented.